Minimizing the sum of earliness/tardiness in identical parallel machines schedule with incompatible job families: An improved MIP approach - OMAR, M; TEO, S (ELSEVIER SCIENCE INC, 2006)
This research considers the problem of scheduling jobs on a set of identical parallel machines, with distinct due dates, process time and early due date restrictions. Further more, the jobs originate from incompatible product families, making it a sequence-dependent setup every time a job is switched from one family to another. Based on the policy that discourages both jobs being early as well as late, we focus on minimizing the sum of earliness/tardiness in the presence of setups. We developed a mixed integer programming formulation model to deal with such scheduling problems. The model can provide optimal solutions for up to 18 jobs that originate from up to four incompatible families. (c) 2006 Elsevier Inc. All rights reserved.